In vitro Antioxidant Activity of Methanolic and Ethanolic Extracts of seeds of Macrotyloma uniflorum - Parasuraman, Subramani; Raipan, Vanishya A/P (Free Radicals and Antioxidants)
Objectives: To study the antioxidant activity of methanolic and ethanolic extracts of seeds of Macrotyloma uniflorum. Methods: The seeds of M. uniflorum were extracted with methanol and ethanol and used for the phytochemical analysis and determination of antioxidant activity. The in vitro antioxidant activity was studied using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydroxyl radical scavenging methods. Result: Ethanolic extracts of M. uniflorum showed more phenolic content (63.48 mg GAE/g) than methanolic extract of M. uniflorum (45.84 mg GAE/g). In total flavonoid content analysis, methanolic and ethanolic extracts of M. uniflorum showed the presence of flavonoid content of 15.31 mg Rutin/g and 15.44 mg Rutin/g, respectively. In DPPH assay, methanolic and ethanolic extracts of M. uniflorum exhibited 50% free radical scavenging activity at 797.71 ± 34.38 μg/mL and 938.80 ± 66.05 μg/mL (mean ± standard deviation; n = 3), respectively. In hydroxyl radical scavenging assay, methanolic and ethanolic extracts of M. uniflorum exhibited 50% fee radical scavenging activity at 770.27 ± 11.64 μg/ mL and 844.94 ± 35.12 μg/mL (mean ± standard deviation; n = 3), respectively. Ascorbic acid exhibited potent free radical scavenging with IC50 value of 60.54 ± 5.23 μg/mL in DPPH method and 207.98 ± 14.26 μg/mL (mean ± standard deviation; n = 3) in hydroxyl radical scavenging method. Conclusion: Ethanolic extracts of M. uniflorum showed more phe- nolic content than methanolic extract of M. uniflorum. In both, DPPH and hydroxyl radical scavenging assay, methanolic and ethanolic extracts of M. uniflorum exhibited antioxidant activity at higher concentration.
Keywords: 2; 2-diphenyl-1-picrylhydrazyl (DPPH); Free radical; Hydrogen peroxide (H2O2)